LONG - TERM VARIATIONS IN THE F- AND D-REGIONS OF IONOSPHERE - Gordiyenko, G.I.; Yakovets, A.F.; Yakovets, A.F.; Litvinov, Yu.G. (Academic Scientific Journal of Computer Science, 2020)
The long-term changes in the near-noon, diurnal, and midnight critical frequencies of the ionosphere F2 layer (foF2) and near-noon minimum reflection frequencies (fmin) were studied using ground-based vertical radio sounding of the ionosphere at Alma-Ata station [43.25N, 76.92E] for the period 1957-2017. The data on solar and geomagnetic activity were used as factors affecting the state of the ionosphere. It was taken into account that the minimum reflection frequency depends both on the absorption of the probe signal in the lower ionosphere, and on the noise level and technical characteristics of the ionosonde. Therefore, it seems problematic to estimate the absolute value of signal absorption in this way. However, as a qualitative characteristic, as an indicator of the absorption level of the probe signal, the parameter fmin can be used. Arithmetic average values of median foF2 for near noon (10-14 LT), near midnight (23-01 LT) hours and average diurnal values for this period of ionosphere observation are considered as initial data. The variability of the lower ionosphere was studied using fmin data for daylight hours. The monthly average values of the solar radio emission flux F10.7 and the Ap index are considered as characteristics of solar and geomagnetic activity. The geomagnetic (Ap) indexes, the near-noon, near-midnight, diurnal averaged foF2, and near-noon fmin variations are found to be in strong dependence from the solar activity; all of them show a dominant pattern of variation with a period of ~34-36 years and linear negative trend. The correlation coefficient between the foF2 and F10.7 long-term variations is very high, up to 0. 99 that permit us to believe that the solar activity can be considered to be the main driver for the long-term variations in the ionospheric F2-region. The geomagnetic (Ap) index, the near-noon, near-midnight, daily averaged foF2, and near-noon fmin variations are found to be in strong dependence from solar activity; all of them show a dominant pattern of variation with a period of ~34-36 years and linear negative trend. The correlation coefficient between the foF2 and F10.7 long-term variations is very high, up to 0. 99, that permits us to believe that the solar activity can be considered as a main driver for the long-term variations in the ionospheric F2-region. The long-term course of fmin is similar to those found in F10.7, Ap, and foF2, i.e. the periodicity of 34-36 years is also evident in the fmin variations. However, in contrast to the F2-layer parameters, the fmin variation clear demonstrates an upward (positive) linear trend that is opposite in sign to the trend found in F10.7. This means relatively high sensitivity of the fmin values to the solar activity changes and significant influence of other trend drivers on them, one of which is the possible impact of anthropogenic factors on the state of the lower ionosphere.